2019
DOI: 10.3389/fmicb.2019.00969
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of DNases by Marine Bacteria: A Culture Based and Bioinformatics Approach

Abstract: The vast majority of bacteria present in the natural environment are present in the form of aggregates and/or biofilms. Microbial aggregates are ubiquitous in the marine environment and are inhabited by diverse microbial communities which often express intense extracellular enzymatic activities. However, the secretion of an important group of enzymes, DNases, by bacteria from marine aggregates has not been studied, despite the importance of these aggregates in biogeochemical cycling of nutrients in the oceans.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…Although we only identified six Bacillus species (B. cereus, B. muralis, B. mycoides, B. pumilus, B. simplex and B. thuringiensis) that produce exDNase, several other Bacillus species have been reported to exhibit extracellular nuclease activity including B. subtilis (Akrigg and Mandelstam 1978;Moreno et al 2012); B. licheniformis (Nijland et al 2010); B. fusiformis, B. megaterium, B. sphericus, B. brevis (Balestrazzi et al 2007); and B. seohaeanensis, B. stratosphericus, B. oceanisediminis, B. mojavensis (Moreno et al 2012). A study by Al-Wahaibi et al (2019) reported the Bacillus genera group to constitute the largest proportion of culturable exDNase-producing bacterial isolates from different marine habitats. However, their findings that Proteobacteria (57%) and Firmicutes (34%) dominated culturable exDNase-producing bacterial isolates contrasts our results as the largest proportion belonged to Firmicutes (54%) while Actinobacteria were the second largest group (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Although we only identified six Bacillus species (B. cereus, B. muralis, B. mycoides, B. pumilus, B. simplex and B. thuringiensis) that produce exDNase, several other Bacillus species have been reported to exhibit extracellular nuclease activity including B. subtilis (Akrigg and Mandelstam 1978;Moreno et al 2012); B. licheniformis (Nijland et al 2010); B. fusiformis, B. megaterium, B. sphericus, B. brevis (Balestrazzi et al 2007); and B. seohaeanensis, B. stratosphericus, B. oceanisediminis, B. mojavensis (Moreno et al 2012). A study by Al-Wahaibi et al (2019) reported the Bacillus genera group to constitute the largest proportion of culturable exDNase-producing bacterial isolates from different marine habitats. However, their findings that Proteobacteria (57%) and Firmicutes (34%) dominated culturable exDNase-producing bacterial isolates contrasts our results as the largest proportion belonged to Firmicutes (54%) while Actinobacteria were the second largest group (20%).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these marine algal-derived fungi grow in an exceptionally extreme and inimitable habitat, which makes them capable to produce unusual secondary metabolites. This is simply because of their existence and adaptation to a distinct ecosystem (Flewelling et al, 2015;Wahaibi et al, 2019). Several studies have previously demonstrated the cytotoxic activities of marine endophytic extracts in cancer cells (Kamat et al, 2020a;Kamat et al, 2020b;Sajna et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nucleases perform different roles to fit bacterial lifestyle ( Al-Wahaibi et al, 2019 ; Pressler et al, 2019 ). Extracellular nucleases are known as enzymes to accommodate invading bacteria in hosts via the formation of a set of diverse oligonucleotides with immunomodulatory properties ( Takahashi et al, 2006 ) or help evade the innate immune response ( Jhelum et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%